ЭНЕРГЕТИЧЕСКАЯ ЭФФЕКТИВНОСТЬ ЗДАНИЙ ПРИ ИСПОЛЬЗОВАНИИ КОМБИНИРОВАННЫХ СИСТЕМ ТЕПЛОСНАБЖЕНИЯ НА ОСНОВЕ ГАЗОПОТРЕБЛЯЮЩИХ КОТЛОВ И ЭЛЕКТРИЧЕСКИХ СИСТЕМ ПРЯМОГО ДЕЙСТВИЯ - Prokopov, V.G. (Institute of Engineering Thermophysics of NAS of Ukraine, 2018)
The evaluation results of the energy efficiency of buildings, provided the use of combined heating systems with traditional water heating and direct action electric heating are submitted. Optimal quantities of heat loss share of buildings, which is compensated by electrical heating, are determined.